The impact of COVID-19 pandemic on divorce rates among Indonesian Muslim societies - Isnawati Rais (IAIN Salatiga, 2021)
This study aims to look at the impact of the COVID-19 pandemic on divorce rates in Indonesia. Few months after the outbreak, the media reported the increasing rate of divorce. Some authorities and researchers have taken this information for granted; therefore, their responses can be misleading. This socio-legal study confronts the media reports with the statistical data on divorce case numbers received by the Religious (Islamic) Courts and the Religious Courts judges’ explanation about the issue. This study finds out that the one-year period (2020) of the COVID-19 pandemic has not influenced the rates of divorce cases submitted to the court. Social mobility restrictions and the inadequate use of the E-Court facility to enhance courts’ performance are among the causes of the crowding of divorce applicants. This implies that the current COVID-19 pandemic has little impact on divorce dynamics despite its significant influence on households’ economic instability and the increasing of domestic violence cases. With a more careful response to the media report, the authorities will be able to address the real issues faced by many households and the judiciary.